The impact of US tariffs against China on US imports - Simone Cigna; Philipp Meinen; Patrick Schulte; Nils Steinhoff (European Central Bank (ECB), 2020)
In this paper we provide evidence on the existence of short-run trade diversion effects towards third countries as a consequence of tariff shocks. We exploit sudden policy changes in the context of the trade dispute between the US and China. Based on a data set covering monthly product-level information on US imports from 30 countries for the period January 2016 until May 2019, we employ a difference-in-differences estimation framework. Doing so, we (1) can confirm previous findings showing a strong negative direct effect of US tariffs on US imports from China, but (2) do not find evidence for significant short-run trade diversion effects towards third countries. This latter finding holds for product and country subgroups as well as for a variety of robustness checks.
Keywords: F13; F14; F61; 330; Tariffs; US imports; trade diversion; product-level data; difference-in-differences